Chemical Bonding of Fe3O4 Nanoparticles on the Surface of Poly(acryloyl chloride) Functionalized Multiwalled Carbon Nanotubes - Pekdemir, Mustafa Ersin; Coskun, Mehmet (Springer International Publishing Ag, 2020)
Poly(acryloyl chloride) (PAC) was first reacted with oxidized MWCNT to form oxidized MWCNT-g-PAC. Then, aminated MNP were bonded to the oxidized MWCNT-g-PAC to form oxidized MWCNT-g-PAC-g-aminated MNP. The chemical characterization for primary and the product materials was performed using FT-IR spectroscopy. SEM images and SEM-EDX were used for the surface morphology and elemental characterization, respectively. Vibrating sample magnetometer measurements showed that aminated MNP and oxidized MWCNT-g-PAC-g-aminated MNP have magnetic saturation values of 52.07 emu/g and 20.38 emu/g, respectively. Both of the two samples indicated the superparamagnetic nature. TGA measurements were accomplished to compare the thermal stability of materials. Also, the DSC measurements were performed to compareT(g)temperatures. While AC conductivity values of the oxidized MWCNT-g-PAC and oxidized MWCNT-g-PAC-g-aminated MNP increased by increasing frequency, it has not changed with increasing temperature. This result indicates that these materials act as electrical insulators.
Keywords: Poly(acryloyl chloride); MWCNT; Fe(3)O(4)nanoparticle; Functionalization; VSM